SINERGI AKTOR STREET LEVEL BUREAUCRACY DALAM PENANGANAN PANDEMI COVID-19 DI KOTA SERANG - Nikki Prafitri; Wahyu Kartiko Utami (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2021)
Synergy between government actors is needed in handling Covid-19. The synergy must reach street level bureaucracy government. This frontline government has an important role in handling Covid-19 both of health and economy sectors. But in its implementation, the case Covid-19 in Serang city continues to increase, adherence to health protocol implementation is still low and there are obstacles in the distribution of economic assistance to the community. These problems can be overcome with good synergy, especially the synergy between levels of the street bureaucracy. The purpose of this study was to determine the synergy between street level bureaucracy actors in handling Covid-19 in Serang City from the aspects of communication, coordination and interaction. The results showed that the synergy between street bureaucracy actors in handling Covid-19 was influenced by the pattern of central and regional government policies, clarity and understanding of roles between actors, conditions of the Covid-19 case in an area and the capacity and local leadership of the street level bureaucracy.